Incidencia del ataque de Hypsipyla grandella zeller (1919) (Lepidoptera: Pyralidae) Barrenador de las meliaceas... - López Flores, Walter Shember (2012)
In Peru there are 74 million hectares of natural forests, 10.5 million hectares of lands with forest aptitude, and only 197,000 hectares of plantations. The low Jungle that understands the Amazonian plain is the least populated sub-region where one finds the majar forest potential that corresponds to the productive heterogeneous forests. In the present take advantage 80 forest species to 14 core products, including cedro and caoba because of its high commercial value. However it has discouraged the planting of these woods, as a result of the proliferation of diverse plagues including Hypsipyla grandella Zeller, compounded by the fact that the economic damage of forest pests tend to increase their economic significance with the passage of time and with the evolution ofthe tree, from its seed stage to mature tree. This research work has as its goal the provide contributions of significan! relevance, on sorne of the considerations that should be taken into account, when it is sought to manage a caoba plantation, for which was raised as a hypothesis that the determination of the incidence of attack of Hypsipyla grandella in plants of Swietenia macrophylla 'mahogany', will allow to program the integrated management of this pest. Its comparison is guided by goals such as: To determine the incidence of attack of Hypsipyla grandella in caoba plants, determination of the optimum height of highest incidence and the influence of climatic conditions in the dynamism ofthis plague. As a result, it was determined that the incidence of attack in caoba plants occurs to the O. 50 m in height in the future, and that the optimum height of highest incidence occurs when the caoba plants reach 2 meters up to 4 meters in height. On the other hand, it was determined that the weather conditions do not play an important role in the dynamism of Hypsipyla grandella; it is assumed that this plague has no precise indicators that determine their activity. The purpose lies mainly in the need to establish plantations with forest species of high economic value and environmental sustainable way free of this pest, especially in areas devastated by the discriminated against and selective removal of species such as caoba. Key words: forest species, high economic value